A creation in abstract 3D art inspired from Pavo muticus imperator - Jirawat Sookkaew; Nakarin Chaikaew; Donticha Chiewsuwan; Somchai Seviset (Institute of Advanced Engineering and Science, 2022)
Creation of art as abstract art by choosing athree-dimensional (3D)art formto be used for creativity, has brought the characteristics of the peacock inspired by its forms, color characteristics, including its habitats to be usedas a mixture and elements in creating this art. Therefore, when combined with the key elements of a 3D object with depth dimension of the object in the Z axis, adopting the colors of the space and the atmosphere of thepeacock's habitat to the surface of the 3D pieces, which provide creative approaches and techniques that enable abstract 3D art to be realized by the shapes and formed by perspectives as a whole. Z-axis can create directions to display hundreds of perspectives. In addition, the colors that have beenused to blend in with the 3D objects create beauty inspired by the colors that can be found in nature. The peacock's art has been passed through with the distinctive features of 3D objects, resulting in creating such abstract 3D artpieces.